HERPESVIRUS REPLICATION: FROM SIMPLE TO COMPLEX - Ziyodova Laylo,; Umarova Tamila Abdufattoevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
In clinical practice, physicians of various specialties frequently encounter diseases caused by viruses of the Herpesviridae family. Currently, eight antigenic serotypes of herpesviruses are known: herpes simplex virus types 1 and 2, varicella-zoster virus, cytomegalovirus, Epstein-Barr virus, and human herpesviruses 6, 7, and 8. Herpesviruses are widely prevalent in the human population and are capable of affecting almost all organs and systems of the host organism, causing latent, acute, and chronic forms of infection. It should be noted that these viruses may play a role in the development of neoplastic processes, such as cervical cancer and prostate cancer, and in the induction of atherosclerosis, where herpes simplex virus may act in association with cytomegalovirus. They can also have adverse, and sometimes fatal, effects on pregnancy and childbirth, as well as neonatal pathology.